Strain Energy Method for Determining Dynamic Yield Stress in Taylor’s Test - Edward WŁODARCZYK; Marcin SARZYŃSKI (Engineering Transactions, 2017)
This paper presents a theoretical method for determining dynamic yield stress of metals. The method is based on conversion of the part initial kinetic energy of a metal rod striking a rigid target into the energy of elastic and plastic-strain deformation at selected period ts. By means of this method, a theoretical simple algebraic formula has been derived for determining the dynamic yield stress of metals loaded by the Taylor direct impact experiment (Taylor DIE). This formula gives the results comparable with experimental data.